Application of Ferrate in Industrial Wastewater Treatment - Van, Do The; Cong, Vo Huu (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1DO - 10.25073/2588-1094/vnuees.5256, 2025)
This study focuses on reviewing the potential of ferrate in industrial wastewater treatment. Industrial wastewater from circuit boards and electronic production, specifically from metal plating, corrosion, and cleaning processes, contain a high level of heavy metals and very complex organic components with a wide range of pH. Coagulants for wastewater treatment such as Polyaluminium chlorite (PAC) and alum have a neutral pH and low efficiency of treating heavy metal and organic matter, especially with the increasingly strict regulations of discharge standards for industrial wastewater. Iron compounds have many different valences such as +2 (FeCl 2 , FeSO 4 , Fe(NO 3 ) 2 …), +3 (FeCl 3 , Fe 2 (SO 4 ) 3 , Fe(NO 3 ) 3 …), +6 (Na 2 FeO 4 , K 2 FeO 4 , CaFeO 4 …) which have the ability to oxidize and are strong coagulants in a wide pH range. It is important to optimize application ratio and conditions such as pH point of wastewater, reaction time, stirring speed and catalysts to achieve the desired effects in wastewater treatment using ferrate. This study provides an overview of the chemical properties and preparation methods of ferrate. In addition, this study also evaluates the basic oxidation capacity of ferrate for treating pollution indicators in wastewater. Keywords: Ferrate, ferrate preparation method, ferrate analysis, ferrate for heavy metal treatment, ferrate for organic matter treatment.